Group Recommender Systems An Introduction - Felfernig, Alexander; Boratto, Ludovico; Stettinger, Martin; Tkalčič, Marko; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents group recommender systems, which focus on the determination of recommendations for groups of users. The authors summarize different technologies and applications of group recommender systems. They include an in-depth discussion of state-of-the-art algorithms, an overview of industrial applications, an inclusion of the aspects of decision biases in groups, and corresponding de-biasing approaches. The book includes a discussion of basic group recommendation methods, aspects of human decision making in groups, and related applications. A discussion of open research issues is included to inspire new related research. The book serves as a reference for researchers and practitioners working on group recommendation related topics.
Part 1. Group Recommendation Techniques -- Decision Tasks and Basic Algorithms -- Algorithms for Group Recommendation -- Evaluating Group Recommender Systems -- Part 2. Group Recommender User Interfaces -- Group Recommender Applications -- Handling Preferences -- Explanations for Groups -- Part 3. Group Decision Processes -- Further Choice Scenarios -- Biases in Group Decisions -- Personality, Emotions, and Group Dynamics -- Conclusions.
Keywords: Telecommunication; Computational intelligence; Artificial intelligence; Image processing -- Digital techniques; Computer vision; Communications Engineering, Networks; Computational Intelligence; Artificial Intelligence; Computer Imaging, Vision, Pattern Recognition and Graphics